Interplay Between Microbiota, Toll-Like Receptors and Cytokines for the Maintenance of Epithelial Barrier Integrity - Semin, Iaroslav; Ninnemann, Justus; Bondareva, Marina; Gimaev, Ilia; Kruglov, Andrey A. (Frontiers in Medicine, 2021)
The intestinal tract is densely populated by microbiota consisting of various commensal microorganisms that are instrumental for the healthy state of the living organism. Such commensals generate various molecules that can be recognized by the Toll-like receptors of the immune system leading to the inflammation marked by strong upregulation of various proinflammatory cytokines, such as TNF, IL-6 and IL-1β. To prevent excessive inflammation, a single layer of constantly renewing, highly proliferating epithelial cells (IEC) provides proper segregation of such microorganisms from the body cavities. There are various triggers which facilitate the disturbance of the epithelial barrier which often leads to inflammation. However, the nature and duration of the stress may determine the state of the epithelial cells and their responses to cytokines. Here we discuss the role of the microbiota-TLR-cytokine axis in the maintenance of the epithelial tissue integrity. In particular, we highlight discrepancies in the function of TLR and cytokines in IEC barrier during acute or chronic inflammation and we suggest that intervention strategies should be applied based on the type of inflammation.